2020
DOI: 10.3920/jiff2019.0051
|View full text |Cite
|
Sign up to set email alerts
|

Can farm weeds improve the growth and microbiological quality of crickets (Gryllus bimaculatus)?

Abstract: Farming of edible insects has been proposed as a means to reduce current practices of harvesting from the wild. While farming could relieve the pressure on wild populations, as well as on their natural habitats, and generate a continuous supply of edible insects to the consumers, the high cost of commercial chicken feeds is still a challenge to many farmers. The aim of this study was to investigate whether the partial replacement of commercial chicken feed with the farm weed, wandering Jew (Commelina sinensis)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…Higher survival rates were documented for A. domesticus reared on diets supplemented with alternative feeds when compared to a control (Sorjonen et al, 2019;Harsányi et al, 2020;Quek et al, 2020). Higher weight gain was recorded in supplemented diets compared to control diets for G. bimaculatus (Ng'ang'a et al, 2020) and A. domesticus (Quek et al, 2020). Ng 'ang'a et al (2020) found that bacterial endospore counts were lower for G. bimaculatus that had been fed chicken feed supplemented with the local weed Commelina sinensis than on a pure chicken feed diet.…”
Section: Supplementationmentioning
confidence: 99%
See 4 more Smart Citations
“…Higher survival rates were documented for A. domesticus reared on diets supplemented with alternative feeds when compared to a control (Sorjonen et al, 2019;Harsányi et al, 2020;Quek et al, 2020). Higher weight gain was recorded in supplemented diets compared to control diets for G. bimaculatus (Ng'ang'a et al, 2020) and A. domesticus (Quek et al, 2020). Ng 'ang'a et al (2020) found that bacterial endospore counts were lower for G. bimaculatus that had been fed chicken feed supplemented with the local weed Commelina sinensis than on a pure chicken feed diet.…”
Section: Supplementationmentioning
confidence: 99%
“…ADF, acid detergent fiber; C, carbohydrate; CF, crude fiber; CP, crude protein; DM, dry matter; NDF, neutral detergent fiber. 2016), microbial counts and relative abundance (Ng'ang'a et al, 2020), maturity period (Oloo et al, 2020), nitrogen efficiency, phosphorus content, total fatty acids (Oonincx et al, 2015), developmental rate, glycoalkaloid concentrations, fatty acid content and composition (Sorjonen et al, 2019), daily DM intake, and periodic FCR (Vaga et al, 2019).…”
Section: Insect Measurementsmentioning
confidence: 99%
See 3 more Smart Citations